Attitudes of GP trainees towards the training received in urology on the GP training scheme. (February 2016) - Redmond, E.; Kelly, N.; McCarthy, C.; Ní Mhurchú, E.; Hayes, H.; Flynn, C.; O'Shea, D.; Giri, S.; Flood, H.
Abstract Introduction The majority of patients with scrotal problems or urinary symptoms will first present to their general practitioner (GP). The importance of the initial examination performed by the GP is often underestimated; however, it frequently determines the course of investigation and ultimately treatment. Unfortunately, medical schools have devoted increasingly less time to teaching urology over the past decade. The impact of this decline in teaching on a GP trainee's assessment of urological complaints remains unclear. The aim of this study was to investigate the self-reported competency of GP trainees in assessing urological presentations. Methods A questionnaire was circulated to 101 GP trainees from five separate training programmes. Respondents rated their confidence in evaluating four different urological presentations. They were also invited to give their opinion regarding the teaching of urology on their current scheme and whether they would be in favour of the addition of urology as an optional rotation. Results Only 18 trainees (19 %) felt urology was adequately covered on their curriculum. A small yet significant number of respondents felt uncomfortable in their assessment of testicular (28 %, 28/101) or prostate (35 %, 35/101) pathology and male (17 %, 17/101) or female (10 %, 10/101) urinary symptoms. Twenty-six trainees (26 %) would choose a rotation in urology if available. Another ten trainees felt that attending urology outpatient clinics would benefit training. Conclusion This study highlights a number of concerns among GP trainees in relation to their training in urology. These issues should be addressed to ensure that the training scheme sufficiently prepares GPs to manage common urological conditions.